ANALISIS PENERAPAN KONSEP MIRANDA RULE DALAM SISTEM PERADILAN PIDANA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Utari Jayu Sahana; Sukmareni Sukmareni; Yon Efri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
In an unbalanced state, the principle of humanism is the most basic aspect. The existence of the Miranda Rule concept is a very concrete concept in the judiciary in Indonesia. This development has turned into a restorative juctice which is implemented from Indonesia towards a judiciary. The nature of the research used is descriptive, namely research that aims to provide data that is as precise as possible about the circumstances that are the object of research. Then the problem approach used is a normative juridical approach, namely research that is only aimed at written regulations so that this writing is closely related to libraries because it will require secondary data from the library. Sources of data and legal materials used are secondary data, namely data obtained through literature studies, including books, supporting literature with the subject matter discussed and laws and regulations. The results of this study are that the Miranda Rule is a rule that regulates the rights of a person who is accused or suspected of having committed a crime/crime, before being examined by an authorized investigator/institution. These rights are in the form of the right to remain silent, because everything said by the suspect can be used against him in court; the right to obtain or contact a legal advisor/advocate to defend general rights; if the person concerned is unable to bring in a legal adviser/advocate, then the institution concerned is obliged to bring in the legal adviser/advocate free of charge. To protect suspects from arbitrary investigative actions, the Criminal Procedure Code regulates the protection of suspects' rights in the process of investigating criminal cases. These rights are regulated in Chapter VI (Article 50 to Article 68) of Law Number 8 of 1981. Legal protection for suspects from actions involving suspects' human rights by investigators is very important.Keywords: Miranda Rules, punishment